Intrapancreatic accessory spleen: A case report and review of literature. Issue 5 (12th January 2012) - Rodriguez, Erika; Netto, George; Li, Qing Kay
Abstract Intrapancreatic accessory spleen is not an uncommon entity and usually located in the tail of the pancreas. Most of them are asymptomatic and incidental findings on radiologic study or at autopsy. On imaging study, it appears to be a well‐defined, solitary, and hypervascular lesion; therefore, it may be confused with pancreatic neoplasms, such as neuroendocrine neoplasm, well‐differentiated adenocarcinoma, solid pseudopapillary tumor, or metastatic tumor to the pancreas. As such, the diagnostic fine‐needle aspiration biopsy of the lesion may be performed. Several case reports describing cytological features of the lesion have been published in recent years. Among them, the most commonly identified cytological findings are sheets of a heterogeneous population of lymphocytes and prominent traversing blood vessels. Herein, we report an unusual EUS‐FNA case of intrapancreatic accessory spleen. In addition to above previously well‐described cytological features, our case revealed many cells with fine granular chromatin and areas with pseudo rosette‐like architecture, mimicking and engendering the differential diagnosis of pancreatic neuroendocrine tumors. Although cytological findings of our case are rare, they may extend our current knowledge and provide additional differential diagnostic information for this entity. Diagn. Cytopathol. 2013. © 2012 Wiley Periodicals, Inc.